Industry–academia interface: the value of collaborative research and development with Danielle Densley Tingley (Communications Engineering)
Professor Danielle Densley Tingley is an environmental engineer based at the University of Sheffield in the UK. Her research focusses on reducing the impact of the built environment on the planet using a number of strategies. Here, Dani shares her perspectives on the benefits of collaborative R&D in building a research career and in addressing grand challenges.